Alleviatory effect of isoquercetin on benign prostatic hyperplasia via IGF-1/PI3K/Akt/mTOR pathway - Young-Jin Choi; Meiqi Fan; Nishala Erandi Wedamulla; Yujiao Tang; Eun-Kyung Kim (Food Science and Human Wellness)
We evaluated the effect of isoquercetin (quercetin-O-3-glucoside-quercetin, IQ) as a functional component of Abeliophyllum disistichum Nakai ethanol extract (ADLE) on prostate cell proliferation and apoptosis and its effects on the IGF-1/PI3K/Akt/mTOR pathway in benign prostatic hyperplasia (BPH). Metabolites in ADLE were analyzed using UHPLC-qTOF-MS and HPLC. IQ was orally administered (1 or 10 mg/kg) to a testosterone propionate-induced BPH rat model, and its effects on the prostate weight were evaluated. The effect of IQ on androgen receptor (AR) signaling was analyzed in LNCaP cells. Whether IGF-1 and IQ affect the IGF-1/PI3K/Akt/mTOR pathway in BPH-1 cells was also examined. The metabolites in ADLE were identified and quantified, which confirmed that ADLE contained abundant IQ (20.88 mg/g). IQ significantly reduced the prostate size in a concentration-dependent manner in a BPH rat model, and significantly decreased the expression of AR signaling factors in the rat prostate tissue and LNCaP cells in a concentration-dependent manner. IQ also inhibited the PI3K/AKT/mTOR pathway activated by IGF-1 treatment in BPH-1 cells. In BPH-1 cells, IQ led to G0/G1 arrest and suppressed the expression of proliferation factors while inducing apoptosis. Thus, IQ shows potential for use as a pharmaceutical and nutraceutical for BPH.